Prevalencia infekcie vírusom hepatídy C v Slovenskej republike - Schréter, I; Kristian, P; Klement, C; Kohútová, D; Jarcuska, P; Madarová, L; Avdicová, M; Máderová, E (Klinicka mikrobiologie a infekcni lekarstvi, 2007)
OBJECTIVE: To assess the prevalence of hepatitis C in the general Slovak population without any further evaluation or risk group stratification. MATERIAL AND METHODS: A total of 3,608 remnant serum specimens from epidemiological surveys in 1997 (1,484 specimens) and 2002 (2,124) were analyzed. These were from randomly selected persons over 15 years of age from all over Slovakia. The anti-HCV antibodies were detected using the 4th generation ELISA test. In case of positive or borderline results, the presence of HCV RNA was determined qualitatively. RESULTS: Of the 3,608 analyzed specimens, 55 (1.52 %) were anti-HCV-positive and 10 (0.28 %) were borderline positive. HCV RNA was detected in 24 cases (0.67 %). A comparison of the 1997 and 2002 results showed a statistically significant (p < 0.01) increase of anti-HCV-positive specimens. A similar--but not significant--increase was noted in HCV RNA-positive cases. Despite a slightly higher prevalence of HCV infection in females, no statistically significant gender differences were found. Whereas anti-HCV positivity increased slightly with age, most HCV RNA patients were from the middle age group, i.e. between 36 and 45 years of age. The geographic distribution of HCV cases across Slovakia was relatively even. CONCLUSIONS: The prevalence of anti-HCV antibodies in subjects representing the general population of Slovakia older than 15 years was 1.52 %; chronic HCV infection was confirmed in 0.67 % of cases.
Keywords: RNA, Viral; hepatitida C; RNA virová; Male; Slovakia; Seroepidemiologic Studies; Slovenská republika; séroepidemiologické studie; Adolescent; Adult; prevalence; Aged; dospělí; Hepacivirus; mužské pohlaví; senioři; mladiství; lidé; ženské pohlaví; Humans; Hepatitis C; Prevalence; Hepatitis C Antibodies; hepatitida C - protilátky; Female; lidé středního věku; Middle Aged